Extradural spinal Rosai-Dorfman disease with paravertebral involvement. Case report - Cueva Núñez, Manuel; Yábar Boza, David; Soto Padilla, Pedro; Contreras Montenegro, Luis Enrique (Revista Argentina de Neurocirugía, 2026)
Introduction: Rosai-Dorfman disease (RDD) is a benign, idiopathic, proliferative, histiocytic disorder, characterized by sinus histiocytosis and massive lymphadenopathy. Rosai and Dorfman described four cases in 1969 which they called sinus histiocytosis with massive lymphadenopathy, the entity of which is different from histiocytosis X and can be found both in lymph nodes and extranodal organs or tissues. It is a relatively rare entity in its classic lymph node presentation, even more so in its extranodal form. The incidence described in USA is 100 cases per year, the extranodal presentation is approximately 35% of the cases, less than 5% involving the CNS. Objective: to describes and present the case of a type of non-neoplastic lesion rarely referred in the literature and that may have a good prognosis. Case description: we present the case of a young patient with extranodal RDD that compromised the spinal region causing a clinical presentation of spine cord compression characterized by paraplegia, loss of sensitivity below the lesion and loss of sphincter control. Surgery: T2-T6 laminectomy with macroscopically complete tumor excision and subsequent clinical improvement. Conclusion: RDD is an histiocytic disorder of probable immune etiology secondary to a viral infectious response, it presents in its classic form involving mainly cervical lymph nodes, as well as in its extranodal form in which the lymphoid system may or may not be compromised, more frequent CNS involvement compromises the brain, less often the spinal cord.